2013
DOI: 10.1091/mbc.e12-07-0561
|View full text |Cite
|
Sign up to set email alerts
|

RNA polymerase II progression through H3K27me3-enriched gene bodies requires JMJD3 histone demethylase

Abstract: JMJD3 H3K27me3 demethylase plays an important role in the transcriptional response to different signaling pathways; however, the mechanism by which it facilitates transcription is unclear. Genome-wide analysis shows that JMJD3 regulates TGFβ response by promoting RNA polymerase II progression along the gene bodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 44 publications
6
47
0
1
Order By: Relevance
“…Previous results also suggested that KDM6B activates gene transcription by promoting transcriptional elongation, which is associated with RNA polymerase II and related elongation factors [25,26]. These results indicated that up-regulation of KDM6B should be essential for gene expression of specific hypoxia response gene under hypoxia.…”
Section: Discussionmentioning
confidence: 68%
“…Previous results also suggested that KDM6B activates gene transcription by promoting transcriptional elongation, which is associated with RNA polymerase II and related elongation factors [25,26]. These results indicated that up-regulation of KDM6B should be essential for gene expression of specific hypoxia response gene under hypoxia.…”
Section: Discussionmentioning
confidence: 68%
“…Our previous work with the TD model showed that upon C/EBP␣ induction, there is a gradual loss of H3K27me3 at C/EBP␣ binding sites, particularly at de novo enhancers that harbor high levels of H3K27me3 and low levels of H3K4me prior to induction (14 linked to active Pol II elongation (20,31,32), an event critical for the establishment of LTTM (Fig. 4A).…”
Section: Resultsmentioning
confidence: 95%
“…Moreover, removal of H3K27me3, an EED-binding target, will destabilize binding of PRC2 itself, potentially initiating a negative feedback loop augmented by the incurrence of symmetric H3K4me3 when transcription commences. Notably, JMJD3 has also been implicated in regulating the release of paused RNA Pol II into productive elongation, traveling along the gene body to clear H3K27me3 (Chen et al 2012;Estará s et al 2013). With respect to removal of PRC1 and deubiquitinylation of H2A, multiple proteins have been identified that possess deubiquitinylation activity toward H2A in mammals, including MYSM1, USP3, USP7, USP16, USP21, and USP22 (Weake and Workman 2008;Atanassov et al 2011).…”
Section: Resolution Of Bivalent Domains During Differentiationmentioning
confidence: 99%